Cardiovascular extracellular microRNAs: emerging diagnostic markers and mechanisms of cell-to-cell RNA communication - Kinet, virginie; Halkein, Julie; Dirkx, Ellen; De Windt, Leon J. (Frontiers in Genetics, 2013)
Cardiovascular diseases are a leading cause of morbidity and mortality in Western societies. It is now well established that microRNAs (miRNAs) are determinant regulators in various medical conditions including cardiovascular diseases. The recent discovery that miRNAs, while associated with different carriers, can be exported out of the cell, has triggered a renewed interest to analyze the potential to use extracellular microRNAs as tools for diagnostic and therapeutic studies. Circulating miRNAs in biological fluids present a technological advantage compared to current diagnostic tools by virtue of their remarkable stability and relative ease of detection rendering them ideal tools for noninvasive and rapid diagnosis. Extracellular miRNAs also represent a novel form of inter-cellular communication by transfering genetic information from a donor cell to a recipient cell. This review briefly summarizes recent insights in the origin, function and diagnostic potential of extracellular miRNAs by focusing on a select number of cardiovascular diseases.